Using local ecological knowledge to identify land-use threats to the last wild population of the Chinese alligator Alligator sinensis - Erika Y. X. Lau; Josh A. Hodge; Jonathan P. Rio; Tao Pan; Philip D. Mannion; Samuel T. Turvey (Oryx)
Conservation management in human-modified landscapes requires information on the sustainability of interactions between people and biodiversity. Wild Chinese alligators Alligator sinensis only persist within the National Chinese Alligator Reserve in south-eastern China, where they live alongside agricultural communities that utilize local terrestrial and wetland habitats. We conducted an interview survey of communities within and around the Reserve to evaluate whether local ecological knowledge can provide a baseline on the species' local status and trends, and to understand the relationships between land-use practices and alligator presence and survival. Respondents within the Reserve were more likely to recognize alligators, report sightings and perceive declines than other respondents. Absolute levels of knowledge and experience of alligators were low, highlighting the species' perilous status, and analysis of correlative patterns between respondents' experiences and associated data on human–environmental interactions provides new conservation-relevant insights. Alligator sightings were more likely to be reported by respondents who did not grow crops, and eggs and nests by those who did not utilize local water sources for irrigation, suggesting that existing environmental pressures associated with agriculture may be unsustainable for alligators. Although respondents who lived outside the Reserve were more likely to use agrochemicals, we found no relationship between pesticide or fertilizer usage and variation in respondent awareness or experience of alligators. Our findings indicate that China's last wild alligators continue to experience negative human pressures, and current land-use practices are probably incompatible with long-term alligator survival.